PROSPECTS FOR THE FORMATION OF A MULTIPOLAR WORLD - Матназарова Муниса Шухратовна (Journals Park Publishing, 2024)
This scientific article examines multipolar political systems based on the concept of a new world order. The role of various countries and international organizations in a multipolar system is revealed. At the same time, the foreign policy of modern Uzbekistan and its main directions are analyzed.
Keywords: Multipolar world, world politics, competitive environment, Republic of Uzbekistan, international organizations, reforms.